Odgovornost zaščititi v teoriji in praksi - Pirc Musar, Nataša (Pravnik, 2023)
In her opening address, the President of the Republic of Slovenia, Nataša Pirc Musar, stated that Slovenia has always been a strong supporter of the Responsibility to Protect (R2P) and was part of a group of countries that co-created this important principle nearly two decades ago. President Pirc Musar also identified climate change as one of the (new) factors of instability and war, concluding that the concept of climate justice is gaining traction in the international community. At the very core of the Responsibility to Protect is the recognition that the promotion and protection of human rights do not stop at national borders. While States have a primary responsibility to protect the population on their territory, the international community shares the responsibility to protect vulnerable groups from most egregious violations of their universal human rights.
Keywords: človekove pravice; etnično čiščenje; genocid; mednarodno pravo; odgovornost zaščititi; podnebna pravičnost; uvodniki; vojna hudodelstva